Persepsi Wajib Pajak UMKM Atas Peraturan Pemerintah Nomor 23 Tahun 2018 Di Kota Pontianak - Renny Wulandari Risal (LPPM University 17 Agustus 1945 Samarinda, 2021)
This research aims to analyze and provide an overview of the perception of SMEs taxpayers in Pontianak City towards Government Regulation No. 23 of 2018 which is seen from tax rates, techbologyÂ and tax information, tax sanctions, tax facilities and tax socialization. This research is a descriptive study that describes the perception of taxpayers towards Government Regulation No. 23 of 2018. The sample in the study of SMEs taxpayers in Pontianak City uses the convenience samplling technique. The data analysis technique used validity test, reliability tets and descriptive data analysis. The results of that the perception of SMEs taxpayers on Government Regulation No. 23 0f 2018 as awhole has not been optimal. However, for taxpayer Government Regulation No. 23 of 2018 has provided convenience in carrying out tax payments for SMEs.